Kegiatan Peningkatan Kemampuan Literasi Dan Numerasi Melalui Buku Cerita Berbasis Budaya Indragiri Hulu Di SD Negeri 012 Beringin Jaya - Alim, Jesi Alexander; Hermita, Neni; Alpusari, Mahmud; Marhadi, Hendri; Erlisnawati, Erlisnawati; Fendrik, Muhammad; Siregar, Siti Nuranisah; Qibtia, Maryatul; Septiana, Lora; Dita, Rokiya (Unri Conference Series: Community Engagement, 2024)
The service activity was carried out with the aim of improving students’ literacy and numeracy skills at state elementary school 12 Beringin Jaya through the use of storybooks based on Indregiri Hulu culture. Literacy anda numeracy are basic skills that are very important for elementary school students to master as a foundation for learning at a more advanced level. However, conventional approaches are often less able to attract students’ interest, especially when the material presented is not directly related to their environment or culture. To overcome this, this activity develops and implements a storybooks that integrates Indragiri Hulu culture values. This storybook is designed not only to strengthen reading and counting skilss, but also to foster a sense of love and pride for local cultural heritage. The result of this service showed a significant improvement in students’ literacy and numeracy skills, as well as an increase in their local cultural awareness. Overall, this activity is expected to make a positive contribution to the development of education at state elementary school 012 Beringin Jaya and become a model that can be replicated in other schools in Indragiri Hulu and surrounding areas.